Measurement and determination of local film cooling performance along a transonic turbine blade tip with viscous dissipation. (1st June 2022) - Ligrani, Phillip M; Collopy, Hallie; Manneschmidt, Ward
Abstract: Presented are experimental and analytic procedures for the measurement and determination of film cooling performance parameters for a transonic flow environment along a turbine blade tip, which account for the influences of viscous dissipation. Such viscous dissipation magnitudes are vital to ascertain appropriate driving temperatures for convective heat transfer within high velocity, compressible environments. A key step in this procedure is the separation of adiabatic surface temperature magnitudes due to the thermal field from adiabatic surface temperature values associated with flow effects related to viscous dissipation. These latter adiabatic surface temperature magnitudes, from flow effects only, are determined with no film cooling, which, when considered relative to flow stagnation temperature, are directly related to local Mach number values within the tip gap flow along the blade tip surface. After the separation is implemented, adiabatic surface temperature variations from film cooling thermal effects only are provided relative to local baseline values with no film cooling. Resulting local adiabatic film cooling effectiveness and local heat transfer coefficients are subsequently determined which are based entirely upon locally measured temperatures (without the use of global temperature parameters), which is the most appropriate perspective for presentation of spatially-resolved surface heat transfer characteristics. Associated data are provided for the surface of a blade tip with a squealer rim and recess, with and without film cooling. An array of five film cooling holes, located along the upper pressure side of a two-dimensional turbine blade, are employed to provide the film coolant, with a local blowing ratio BR of 3.02. Ratios of tip gap to true blade span are 0.66%, and 1.16%. Experimental procedures employed to obtain the spatially-resolved surface data include infrared thermography, transient testing techniques, and the impulse response method for transient data analysis.